2015
DOI: 10.1134/s0965545x15030049
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity and dielectric relaxation in crosslinked PVA by oxalic and citric acids

Abstract: In this work we investigated polyvinyl alcohol films which we crosslinked at various crosslinking degrees by oxalic and citric acids for the fuel cell applications. We studied the effects of the crosslinking on structure, thermal properties, electric conductivity and dielectric relaxations. The glass transition tempera ture is increased indicating the lowering of the local mobility of the polymer chains. X ray diffraction showed the presence of non dissociated acid phases in dried samples. The Dc conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…[5,51] Based on the physicochemical properties of cross-linked PVA, it has been used in drug delivery, [52] tissue engineering, [43,53] wound dressing, [54] food packaging, [45] antibacterial membrane against the polluted air, [55,56] in desalination of water as reverse osmosis (RO) membrane, [57] pervaporation process, [58,59] filtration/separation of metal ions, [60] and solid polymer electrolytes. [61][62][63] As mentioned above, a number of studies have been reported on carboxylic acid cross-linked PVA. These studies generally focus on the application of carboxylic acid cross-linked PVA on a specific field such as pervaporation, RO, wound dressing, drug delivery, and fuel cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,51] Based on the physicochemical properties of cross-linked PVA, it has been used in drug delivery, [52] tissue engineering, [43,53] wound dressing, [54] food packaging, [45] antibacterial membrane against the polluted air, [55,56] in desalination of water as reverse osmosis (RO) membrane, [57] pervaporation process, [58,59] filtration/separation of metal ions, [60] and solid polymer electrolytes. [61][62][63] As mentioned above, a number of studies have been reported on carboxylic acid cross-linked PVA. These studies generally focus on the application of carboxylic acid cross-linked PVA on a specific field such as pervaporation, RO, wound dressing, drug delivery, and fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,51 ] Based on the physicochemical properties of cross‐linked PVA, it has been used in drug delivery, [ 52 ] tissue engineering, [ 43,53 ] wound dressing, [ 54 ] food packaging, [ 45 ] antibacterial membrane against the polluted air, [ 55,56 ] in desalination of water as reverse osmosis (RO) membrane, [ 57 ] pervaporation process, [ 58,59 ] filtration/separation of metal ions, [ 60 ] and solid polymer electrolytes. [ 61–63 ]…”
Section: Introductionmentioning
confidence: 99%
“…Available studies in the literature showed that PVA films lose their mechanical properties at temperatures well below 100 °C [27]. The combination we propose in this work, cross-linking with oxalic acid and the addition of clay as a reinforcing agent, plays a positive role in improving the mechanical properties of the composite and widening the temperature range of use [15]. A similar result consisting in the increase of the Young's modulus has been observed in Nafion films reinforced with up to 20% of montmorillonite clay [28].…”
Section: Dynamic Mechanical Analysismentioning
confidence: 73%
“…To avoid this problem, many approaches have been adopted to prepare composite polymers based on pure PVA and/or modified PVA. The modification of PVA is achieved by a cross-linking process involving the lateral hydroxyl group (OH) via an acid/base reaction by using a carboxylic di-acid such as the oxalic acid; this process is described in our earlier work [15].…”
Section: Introductionmentioning
confidence: 99%
“…The value of the activation energy for pure PVA is equal to the value reported by Hdidar et al 42 and corresponds to the activation energy of disordered polymer material. 59 As shown in the Figure 6 B, the activation energy is decreasing with the increase in the glycerol content. This could be explained by the increase of the amorphous phase and the softening of the polymer matrix (values summarized in Table 2).…”
Section: Dsc Analysismentioning
confidence: 76%